Pengaruh Terapi Aktivitas Kelompok dengan Stimulasi Persepsi terhadap Kemampuan Mengontrol Halusinasi pada Pasien Skizofrenia - Widya Sepalanita; Wittin Khairani (Jurnal Ilmiah Universitas Batanghari Jambi, 2019)
The prevalence of mental emotional disorders indicated by symptoms of depression and anxiety for ages 15 years and over reaches around 14 million people or 6% of the total population of Indonesia. While the prevalence of severe mental disorders, such as schizophrenia, reaches around 400,000 people or as many as 1.7 per 1,000 residents. Hallucinations are one of the symptoms of schizophrenic mental disorder. Therapy Activities Groups with perceptual stimulation are therapies that use activities to perceive various stimulations related to experience with life to be discussed in groups. The aim of the research was to know the effect of group activity therapy on hallucinogenic control ability in schizophrenic patients in Jambi Province Mental Hospital in 2018. This study used a quasi experimental design with a design of one group design with pretest and posttest. The study was conducted at the Jambi Province Mental Hospital in June-September 2018 with a total sample of 30 people taken by purposive sampling. The results of this study are that there is a significant effect of group activity therapy on hallucinogenic control ability in schizophrenic patients at Jambi Province Mental Hospital. This study is expected to increase knowledge, understanding and skills of mental nurses in treating or treating schizophrenic patients, to improve the ability to control the hallucinations of schizophrenic patients through therapeutic activities of perception simulation groups by applying group activity therapy.